2022
DOI: 10.37680/qalamuna.v14i1.1259
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Benefits and Obstacles of Online Learning During the Covid-19 Pandemic in Efl Students' Experiences

Abstract: since the Covid-19 outbreak all of the institutions in Indonesia are forced to use online learning. The sudden use of online learning causes many obstacles. There are many previous studies explored the obstacles of online learning. However, this present study aims to find out the benefits and obstacles from the students’ experiences during online learning in the pandemic Covid-19. This present study is a qualitative research design which is used thematic analysis. Since the students’ characteristics and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
8
1
3
Order By: Relevance
“…The weakness of students in responding and interacting with eLearning is due to the lack of proficiency in the skills to use it, and the university does not offer courses to train them in investing time skills. This finding aligns with some studies, such as the study of Alqudah et al [4], Borayah, Aqoon [17], Herwiana, Laili [18]. However, the study of Rashid, Yadav [16] does not align with the result of this study, which indicated that students had skills to use the platform and navigate to get information about the subject content.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The weakness of students in responding and interacting with eLearning is due to the lack of proficiency in the skills to use it, and the university does not offer courses to train them in investing time skills. This finding aligns with some studies, such as the study of Alqudah et al [4], Borayah, Aqoon [17], Herwiana, Laili [18]. However, the study of Rashid, Yadav [16] does not align with the result of this study, which indicated that students had skills to use the platform and navigate to get information about the subject content.…”
Section: Discussionsupporting
confidence: 76%
“…These results show that undergraduate students have a negative perspective on eLearning. The recent study's results are inconsistent with previous studies' outcomes, such as Alqudah, Jamal, Saleh, Khader, Obeidat [4], that stated that participants were dissatisfied with eLearning as the sole method [18] and [3]. Learning online from the students' perspectives has positively influenced Corona Pandemic.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, researchers were able to observe learning using google meet twice. So it can be observed that in the two meetings students had a strong argument that they had difficulty joining google meet because the network was unstable, besides that for the same reason they also turned off their camera features, so that learning seemed to only run in one direction (Herwiana & Laili, 2022), the lecturer gave material without having two-way interaction with students.…”
Section: Obstacles Faced By Students and Lecturersmentioning
confidence: 99%